PERLINDUNGAN HUKUM BAGI TENAGA KERJA TERHADAP PENDAFTARAN SISTEM BPJS KETENAGAKERJAAN - Chaerrulloh, Fahri; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
This research is expected to discuss how the law can play a role in protecting employees. The Indonesian state has a program that is used as a social safety net or what we often call BPJS. BPJS itself is a Social Security Organizing Agency consisting of BPJS Labor and BPJS Kesehatan, intended for all employees in Indonesia. BPJS TK consists of Old Age Security (JHT), Work Accident Security (JKK), Death Security (JKM) and Pension Security (JP). The absence of restrictions in inputting employee salaries to the BPJS TK SIPP system allows companies to manipulate employee salaries that are not appropriate for workers. Unlike what is done by BPJS Health through the E-Dabunya system, there is a minimum salary input in accordance with the minimum wage of the company's domicile. Data integration is the key to the solution at hand, by both including the Population Identification Number (NIK) should be a gateway to data matching between SIPP BPJS TK and E-Dabu BPJS Kesehatan.Keywords:  BPJS TK, SIPP BPJS TK, Employment.